Penentuan Parameter Optimal Kendali Greenhouse Berbasis Fazi Dan Pid Menggunakan Algoritma Genetika - Tamrin . (PERTETA, 2008)
The development of the control system of adaptive biological-environment was equipped with the optimization technique of'Genetic Algorithm in solving the problem of optimizing parameters. Optimizing the determination ofparameters of fuzzy control and PID were carried out by stimulating the real noise from solar irradiation in greenhouse, such as fluctuation of solar radiation in day time. The parameters of optimal control were determined by minimizing the cumulative square error for each physical unit, such as temperature and humidity with the fitness function which was reciprocally arranged. The performance ofcontrol system was better with the availability ofgenetic algorithm, and therefore the mode of fuzzy control and PID could be used to control the whole biological-environment. The fuzzy parameters for temperatures were P1=O. 17, P2=O.32, P3=11.28, P4=4.58, and P5=141.89, for humidity P1=O.38, P2=O.05, P3 =6.96, P4 =11.73, and P5=968.65; whereas the PID parameter for temperature were Kp=O.06, TD=O.08, and TD=1.91, for humidity were Kp=O.01, TD=O.0012, and TD=16.Keywords: optimal parameter, fuzzy control, PIO control, genetic algorithmDiterima: 21 Januari 2008; Disetujui: 27 Mei 2008